Tata Ruang pada Rumah Pengrajin Gamelan sebagai Home Industry di Desa Wirun Mojolaban Sukoharjo - Leny Pramesti; Musyawaroh Musyawaroh (Universitas Sebelas Maret Surakarta, 2024)
A house is a building that functions as a residence or dwelling and as a means of family development. A house should not be considered solely from a quantitative aspect through its physical prospect but also needs to encompass the social and economic aspects of the family. Additionally, a house can extend its function as a place of business and production. Gamelan artisans in the village of Wirun, Mojolaban, Sukoharjo Regency, carry out production activities alongside family development activities. The spatial layout of the gamelan artisans’ homes varies according to their residential and business activities. This study uses a qualitative descriptive method, beginning with field observations of gamelan home industries to obtain detailed descriptions of their spatial layout, information on space utilization, and activities occurring within. This information was gathered through interviews with local residents. The study reveals the impact of industrial activities on the spatial arrangement patterns in the homes of gamelan artisans in Wirun.